Effects of Mental Health Literacy, School Social Support, and Academic Self-Efficacy on Psychological Well-Being of YAPIM Biru-Biru High School Students - Monika Nina Ginting; Sulastri Br Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
This study aimed to analyze the influence of mental health literacy, school social support, and academic self-efficacy on the psychological well-being of students at SMA YAPIM Biru-Biru, Sibiru-Biru District, Deli Serdang Regency. This study employed a quantitative approach with a cross-sectional survey design. The population consisted of all 140 students of SMA YAPIM Biru-Biru, and all were selected as the sample using total sampling technique. Data were collected on February 17–20, 2026, through Likert-scale questionnaires. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results showed that mental health literacy had a positive and significant effect on students’ psychological well-being. School social support also had a positive and significant effect on psychological well-being. Likewise, academic self-efficacy was found to have a positive and significant effect on students’ psychological well-being. Simultaneously, mental health literacy, school social support, and academic self-efficacy significantly influenced students’ psychological well-being. The coefficient of determination indicated that these three independent variables contributed 42.0% to students’ psychological well-being, while the remaining 58.0% was influenced by other factors outside the study.